Parthenogenesis in a captive Asian water dragon (Physignathus cocincinus) identified with novel microsatellites. - Kyle L Miller; Susette Castañeda Rico; Carly R Muletz-Wolz; Michael G Campana; Nancy McInerney; Lauren Augustine; Celine Frere; Alan M Peters; Robert C Fleischer (PLoS ONE, 2019)
Reptiles show varying degrees of facultative parthenogenesis. Here we use genetic methods to determine that an isolated, captive female Asian water dragon produced at least nine offspring via parthenogenesis. We identified microsatellites for the species from shotgun genomic sequences, selected and optimized primer sets, and tested all of the offspring for a set of seven microsatellites that were heterozygous in the mother. We verified that the seven loci showed high levels of polymorphism in four wild Asian water dragons from Vietnam. In all cases, the offspring (unhatched, but developed eggs, or hatched young) had only a single allele at each locus, and contained only alleles present in the mother's genotype (i.e., were homozygous or hemizygous). The probability that our findings resulted from the female mating with one or more males is extremely small, indicating that the offspring were derived from a single female gamete (either alone or via duplication and/or fusion) and implicating parthenogenesis. This is the first documented case of parthenogenesis in the Squamate family Agamidae.